Pengelolaan Informasi Dalam Pengambilan Keputusan Kepala Sekolah Serta Dampaknya Terhadap Efektivitas Pembelajaran - Hartini Hartini; Heri Heri (Jurnal Online Manajemen ELPEI, 2021)
This study aims to determine and analyze the effect of the information management function on the effectiveness of learning in elementary schools in Kindang District, Bulukumba Regency. The type of research used is a quantitative method that emphasizes the objective measurement aspects of social phenomena. The population in the study were employees/employees and all teachers at elementary schools in the Kindang District. Data collection techniques used are interviews, questionnaires, and documentation. Data analysis used descriptive analysis and multiple regression analysis. The test results show that the influence of information management together has a significant (significant) effect on the performance of elementary school employees/teachers in the Kindang District. This can be seen from the planning function, where before formulating a work program, it first implements policies, procedures and standards that must be achieved, then carries out activity planning by first coordinating with staff and employees and always adjusting planning materials. The organizing function, even though it shows a positive effect due to the selection and placement of employees and the assignment of clear assignments, coupled with the conditions of supporting facilities and infrastructure, therefore this function does not have a positive and significant effect. While the evaluation variable, although it has a positive effect, is not significant on the effectiveness of learning.